DETERMINANT FACTORS ENTREPRENEURIAL LIFE SKILLS IN ISLAMIC BOARDING SCHOOLS WITH COMMUNITY TRAINING CENTRES: AN ANP CASE STUDY - Agus Gunawan; Haudh Al Maa'uun; Ssonko Muhammedi; Siti Zahra Khoirunnisa; Muhamad Amin (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
The Islamic boarding school that organises the community work training centre is a collaborative program to help students improve their life skills and achieve entrepreneurial independence. The purpose of the study was to analyse the priority factors of entrepreneurial life skills in Islamic boarding schools that organised community work training centres. The research uses a qualitative method with a case study approach. A sample was collected using purposive sampling at the Raudlatul Athfal Islamic boarding school in Serang Regency, the organiser of the community work training centre. The informant is the manager of the community work training centre, as well as the trainee and manager of the Islamic boarding school. Data collection involves the use of questionnaires, interviews, and literature studies, and the testing of validity through triangulation of the sources. The data analysis uses descriptive statistics, while the technique uses the Analysis Network Process (ANP) with Super Decision. The study's findings indicate that the factors influencing entrepreneurial life skills encompass academic, rational thinking, self-awareness, social, and vocational aspects. Knowing yourself is a priority factor in determining entrepreneurial life skills at Islamic boarding schools that organise community work training centres. This research has implications for the significance of strengthening the aspect of self-knowledge in the development of entrepreneurial life skills in Islamic boarding schools that organise community work training centres. Its limitations include limited coverage of areas and samples, as well as the use of qualitative approaches. Further research is suggested to expand the area, use quantitative methods, and develop more standardised life skill assessment instruments.